2002
DOI: 10.1021/ac011096y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lipoproteins by Capillary Zone Electrophoresis in Microfluidic Devices:  Assay Development and Surface Roughness Measurements

Abstract: The development of a new assay for lipoproteins by capillary electrophoresis in fused-silica capillaries and in glass microdevices is described in this paper. The separation of low-density (LDL) and high-density (HDL) lipoproteins by capillary zone electrophoresis is demonstrated in fused-silica capillaries with both UV absorption and laser-induced fluorescence detection. This separation was accomplished using Tricine buffer (pH 9.0) with methylglucamine added as a dynamic coating. With UV detection, LDL elute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 43 publications
(53 reference statements)
1
46
3
Order By: Relevance
“…The roughness of the Ni master was found to have a maximum height of ~80 μm and an average roughness (R) of 170 nm for the Ni disk itself, 210 nm for the electroplated pattern, and 52 nm for the polished electroplated pattern. The resulting surface roughness of 52 nm is higher than the cases for wet-etched fused-silica capillary or glass CE chip shown in [46]. However, the surface roughness that we have found seems in an acceptable range since we did not experience any experimental difficulties.…”
Section: Physical Characterizationmentioning
confidence: 48%
See 1 more Smart Citation
“…The roughness of the Ni master was found to have a maximum height of ~80 μm and an average roughness (R) of 170 nm for the Ni disk itself, 210 nm for the electroplated pattern, and 52 nm for the polished electroplated pattern. The resulting surface roughness of 52 nm is higher than the cases for wet-etched fused-silica capillary or glass CE chip shown in [46]. However, the surface roughness that we have found seems in an acceptable range since we did not experience any experimental difficulties.…”
Section: Physical Characterizationmentioning
confidence: 48%
“…The surfaces of the microchannels typically have surface roughness values of a few nanometers to a few micrometers [45]. For example, it was found that surface roughness was from 1-11 nm for a fused-silica capillary [46]. Surface roughness does not affect the separation efficiency, however, it increases the relative standard deviation (RSD) of the migration times and peak areas.…”
Section: Physical Characterizationmentioning
confidence: 99%
“…Potential advantages of microchip CE include miniaturization, integration, high-throughput analysis, low reagent consumption, and low cost [12]. Weiller et al [13,14] first utilized microchip CE to separate high-density lipoproteins (HDLs) and LDLs. However, HDL and LDL were not baselineresolved and obtained poor reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the studies reported in the literature, successful analysis of lipoproteins has been achieved only after permanent [12] or dynamic [13] coating of the capillary wall has been applied to suppress adsorption of the particles. Adopting a quite different approach, we have recently demonstrated the usefulness of low-density lipoprotein (LDL) and very low-density lipoprotein (VLDL) particle coatings in lipoprotein oxidation studies by CEC [14,15].…”
Section: Introductionmentioning
confidence: 99%